2020
DOI: 10.3389/fcvm.2020.585309
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Protein Quality Control in Diabetic Cardiomyopathy: From Bench to Bedside

Abstract: Heart failure is a serious comorbidity and the most common cause of mortality in diabetes patients. Diabetic cardiomyopathy (DCM) features impaired cellular structure and function, culminating in heart failure; however, there is a dearth of specific clinical therapy for treating DCM. Protein homeostasis is pivotal for the maintenance of cellular viability under physiological and pathological conditions, particularly in the irreplaceable cardiomyocytes; therefore, it is tightly regulated by a protein quality co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 465 publications
1
11
0
Order By: Relevance
“…Additionally, a lower SIRT3 protein was associated with mitochondrial dysfunction in AD brain [66]. It has been reported that SIRT3 activities were ameliorated by melatonin and icariin administration, resulting in improved mitochondrial function [67]. In addition, SIRT3 inhibits neuroinflammation by removing damaged pro-inflammatory mitochondria and inhibiting the NLRP3 inflammasome [16].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a lower SIRT3 protein was associated with mitochondrial dysfunction in AD brain [66]. It has been reported that SIRT3 activities were ameliorated by melatonin and icariin administration, resulting in improved mitochondrial function [67]. In addition, SIRT3 inhibits neuroinflammation by removing damaged pro-inflammatory mitochondria and inhibiting the NLRP3 inflammasome [16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, upon hyperglycemia and hyperlipidemia, endoplasmic reticulum (ER) stress is invoked by oxidative stress, lipid deposition, and abnormal proteins synthesis in cardiomyocytes ( 60 ). Maladaptive ER stress eventually disturbs lipid synthesis, calcium homeostasis, protein quality control, leading to cell death ( 61 ). FGF21 diminishes ER stress-mediated myocardial apoptosis via reduction of ATF4-C/EBP homologous protein (CHOP) pathway ( 62 ).…”
Section: Fgf21-fgfr1 Signaling In the Heartmentioning
confidence: 99%
“…Impairment of cellular PQC and accumulation of protein aggregates with faulty subcellular organelles leads to the generation of oxidative stress, inflammation, and cell death ( Li et al, 2021 ). These modifications are known to be associated with the impairment of several organ functions and the development of several life-threatening diseases including, CVD, neurological disorders, and premature aging ( Gong et al, 2016 ; Kaur et al, 2020 ). This review will discuss the evolving role of co-chaperone Bcl-2 associated anthanogene protein (BAG5) in UPS, autophagy, mitophagy, oxidative stress, metabolism, and its association with CVDs, Alzheimer’s disease, and Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%